Cranial irradiation increases tumor growth in experimental breast cancer brain metastasis. (1st March 2018) - Hamilton, Amanda M.; Wong, Suzanne M.; Wong, Eugene; Foster, Paula J.
Abstract : Whole‐brain radiotherapy is the standard of care for patients with breast cancer with multiple brain metastases and, although this treatment has been essential in the management of existing brain tumors, there are many known negative consequences associated with the irradiation of normal brain tissue. In our study, we used in vivo magnetic resonance imaging analysis to investigate the influence of radiotherapy‐induced damage of healthy brain on the arrest and growth of metastatic breast cancer cells in a mouse model of breast cancer brain metastasis. We observed that irradiated, but otherwise healthy, neural tissue had an increased propensity to support metastatic growth compared with never‐irradiated controls. The elucidation of the impact of irradiation on normal neural tissue could have implications in clinical patient management, particularly in patients with residual systemic disease or with residual radio‐resistant brain cancer. Abstract : Whole‐brain radiotherapy is the standard of care for patients with breast cancer with multiple brain metastases, and there are negative consequences associated with the irradiation of normal tissue. In our study, we used in vivo magnetic resonance imaging to investigate the influence of radiotherapy‐induced damage of healthy brain on the arrest and growth of cancer cells in experimental breast cancer brain metastasis. We observed that irradiated neural tissue had an increased propensity to support metastatic growth compared with never‐irradiated controls.